Reconceptualising vulnerability and its value for managerial identity and learning. Issue 5 (November 2019) - Corlett, Sandra; Mavin, Sharon; Beech, Nic
Dominant, masculinised constructions of managerial identities are associated with expectations of being in control and strong, and not with vulnerability. Managers may conceal vulnerability and protect themselves through defensive identity work, and such responses may close down learning opportunities. We reconceptualise vulnerability and recognise its value for managerial identity and learning by drawing upon Butler's theory of vulnerability. Analysing interviews with middle and senior managers and presenting our own reflexive learning, we address a lack of empirical accounts of managerial vulnerability. We offer three processes of relational vulnerability: (1) recognising and claiming vulnerability, (2) developing social support to share vulnerability with trusted others, and (3) recognising alternative ways of conceptualising and responding to vulnerability. Rather than defensiveness in the face of vulnerability constructed as weakness, the value of vulnerability lies in its openness and its generative capacity for alternative ways of managerial being and learning.